2003
DOI: 10.1099/mic.0.26476-0
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the gene encoding the ChiB1 chitinase of Aspergillus fumigatus and characterization of a recombinant gene product

Abstract: The gene encoding a major, inducible 45 kDa chitinase of Aspergillus fumigatus was cloned and analysis of the deduced amino acid sequence identified a chitinase of the fungal/bacterial class which was designated ChiB1. Recombinant ChiB1, expressed in Pichia pastoris, was shown to function by a retaining mechanism of action. That is, the b-conformation of the chitin substrate linkage was preserved in the product in a manner typical of family 18 chitinases. Cleavage patterns with the N-acetylglucosamine (GlcNAc)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…Modification of chitin in this compartment might alter the cell wall composition so that filaments do not aggregate and sediment in culture. Such chitin degradation in remnant cell wall material might be similar to autolytic processes observed for ChiB in A. nidulans and ChiB1 in A. fumigatus (65,66). Taking these findings together, U. maydis maintains the expression of one nonconventionally secreted chitinase during its filamentous growth stage, even though its activity is dispensable for morphogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…Modification of chitin in this compartment might alter the cell wall composition so that filaments do not aggregate and sediment in culture. Such chitin degradation in remnant cell wall material might be similar to autolytic processes observed for ChiB in A. nidulans and ChiB1 in A. fumigatus (65,66). Taking these findings together, U. maydis maintains the expression of one nonconventionally secreted chitinase during its filamentous growth stage, even though its activity is dispensable for morphogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…2) (8,10,13,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The sequences share several highly conserved fragments among all chitinases in which three regions are important.…”
Section: Resultsmentioning
confidence: 99%
“…One structural feature, such as that of chitinase B1 from Aspergillus fumigatus (8), contains an extra chitin insertion domain (CID) (9) that comprises Ïł70 -90 amino acids and inserts into the TIM-barrel of CaD. The CID provides residues interacting with a substrate and increases the depth of the substrate binding cleft.…”
mentioning
confidence: 99%
“…Results of phylogenetic analyses of the subfamily of Coccidioides chitinases suggested that Cts2, -3, and -4 were most closely related. Two classes of fungal chitinases have been proposed based upon their structural similarity to family 18 chitinases of plants or bacteria (24). The plantlike fungal chitinolytic enzymes of Coccidioides include Cts2, -3, and -4 (25), which are suggested to function as endochitinases that cleave the chitin chain randomly (44).…”
Section: Discussionmentioning
confidence: 99%